University second language students’ perception of interruptions - Fernández-Amaya, Lucía; López Márquez, Alicia M. (Círculo de Lingüística Aplicada a la Comunicación, 2022)
Although interruptions may negatively affect communication, in the case of second language teaching and learning, they can also be understood as some help from the interlocutor to cover a possible linguistic deficiency on the part of the speaker. In order to examine second language students’ opinion about interruptions, we conducted a survey among 161 Translation and Interpreting students at Pablo de Olavide University (Seville). The results obtained show that students are more annoyed at being interrupted by peers in their second language than in their native language, since they feel that they need more time to formulate their messages and can lose the thread of what they were going to say more easily. It is also observed that a high percentage of respondents do not bother to be interrupted by their teachers, since they interpret this intervention as part of their learning process.